The minimal clinically important difference of the Participation Measurement Scale in chronic stroke - Oyéné Kossi; Soraia M. Silva; Francesco Lena; Mendinatou Agbetou; Thierry Adoukonou; Peter Feys; Félix Nindorera (South African Journal of Physiotherapy)
Background: The Participation Measurement Scale (PM-Scale) is an International Classification of Functioning, Disability and Health-based and Rasch-built scale developed specifically to assess participation in people with stroke.